Large-scale laboratory investigation of pillar-support interaction - Akash Chaurasia; Gabriel Walton; Sankhaneel Sinha; Timothy J. Batchler; Kieran Moore; Nicholas Vlachopoulos; Bradley Forbes (Journal of Rock Mechanics and Geotechnical Engineering)
Underground mine pillars provide natural stability to the mine area, allowing safe operations for workers and machinery. Extensive prior research has been conducted to understand pillar failure mechanics and design safe pillar layouts. However, limited studies (mostly based on empirical field observation and small-scale laboratory tests) have considered pillar-support interactions under monotonic loading conditions for the design of pillar-support systems. This study used a series of large-scale laboratory compression tests on porous limestone blocks to analyze rock and support behavior at a sufficiently large scale (specimens with edge length of 0.5 m) for incorporation of actual support elements, with consideration of different w/h ratios. Both unsupported and supported (grouted rebar rockbolt and wire mesh) tests were conducted, and the surface deformations of the specimens were monitored using three-dimensional (3D) digital image correlation (DIC). Rockbolts instrumented with distributed fiber optic strain sensors were used to study rockbolt strain distribution, load mobilization, and localized deformation at different w/h ratios. Both axial and bending strains were observed in the rockbolts, which became more prominent in the post-peak region of the stress-strain curve.